Deletion of the natural killer cell receptor NKG2C encoding KLR2C gene and kidney transplant outcome - Vietzen, Hannes; Döhler, Bernd; Tran, Thuong Hien; Süsal, Caner; Halloran, Philip F.; Eskandary, Farsad; Herz, Carsten T.; Mayer, Katharina A.; Kozakowski, Nicolas; Wahrmann, Markus; Ely, Sarah; Haindl, Susanne; et al. (Frontiers in immunology, 2022)
Natural killer (NK) cells may contribute to antibody-mediated rejection (ABMR) of renal allografts. The role of distinct NK cell subsets in this specific context, such as NK cells expressing the activating receptor NKG2C, is unknown. Our aim was to investigate whether KLRC2 gene deletion variants which determine NKG2C expression affect the pathogenicity of donor-specific antibodies (DSA) and, if so, influence long-term graft survival. We genotyped the KLRC2wt/del variants for two distinct kidney transplant cohorts, (i) a cross-sectional cohort of 86 recipients who, on the basis of a positive post-transplant DSA result, all underwent allograft biopsies, and (ii) 1,860 recipients of a deceased donor renal allograft randomly selected from the Collaborative Transplant Study (CTS) database. In the DSA+ patient cohort, KLRC2wt/wt (80%) was associated with antibody-mediated rejection (ABMR; 65% versus 29% among KLRC2wt/del subjects; P=0.012), microvascular inflammation [MVI; median g+ptc score: 2 (interquartile range: 0-4) versus 0 (0-1), P=0.002], a molecular classifier of ABMR [0.41 (0.14-0.72) versus 0.10 (0.07-0.27), P=0.001], and elevated NK cell-related transcripts (P=0.017). In combined analyses of KLRC2 variants and a functional polymorphism in the Fc gamma receptor IIIA gene (FCGR3A-V/F158), ABMR rates and activity gradually increased with the number of risk genotypes. In DSA+ and CTS cohorts, however, the KLRC2wt/wt variant did not impact long-term death-censored graft survival, also when combined with the FCGR3A-V158 risk variant. KLRC2wt/wt may be associated with DSA-triggered MVI and ABMR-associated gene expression patterns, but the findings observed in a highly selected cohort of DSA+ patients did not translate into meaningful graft survival differences in a large multicenter kidney transplant cohort not selected for HLA sensitization.
Gesehen am 13.05.2022